Personality traits and negative affect mediate the relationship between cortical thickness of superior frontal cortex and aggressive behavior. (23rd January 2020) - Zhu, Xingxing; Wang, Kangcheng; Cao, Aihua; Zhang, Yong; Qiu, Jiang
Highlights: Aggressive behavior was related to cortical thickness of left superior frontal gyrus. Partial mediation effect of negative affect, especially anger and sadness. Full mediation effect of personality traits, especially agreeableness and neuroticism. Abstract: Aggression reflects the psychological and physical behavior that perpetrator intends to harm victim. Initiation of aggression is influenced by the distal factors (e.g. personality) and proximate causes (e.g. affect) of perpetrator. However, few studies explored the brain structural basis of relationship between these traits and aggressive behavior. In this study, we first explored the association between cortical thickness and aggression in a large young adult sample from the Human Connectome Project. Results found aggressive behavior assessed by the Adult Self-Report was positively correlated with cortical thickness in left superior frontal gyrus (SFG), which was implicated in emotion regulation and executive function. Then, mediation analyses with distal and proximate factors separately showcased that the association between the left SFG thickness and aggressive behavior was partially mediated by negative affect (anger and sadness), and fully mediated by personality traits (agreeableness and neuroticism). Taken together, these experimental findings established dorsal prefrontal cortex as the key region in generating aggressive behavior, and gave a neutral explanation for why individuals with high negative affect and neuroticism exhibit more aggression. This study implicated the possible targeted brain region and behavioral intervention for such at-risk individuals initiating violence.